To simplify the expression \( \frac{3}{10}x + \frac{1}{6}y + \frac{3}{10}x + \frac{3}{6}y \), we can first combine like terms.
-
Combine the \( x \) terms: \[ \frac{3}{10}x + \frac{3}{10}x = \frac{6}{10}x \]
Now simplify \( \frac{6}{10} \): \[ \frac{6}{10} = \frac{3}{5} \] So, \( \frac{6}{10}x = \frac{3}{5}x \).
-
Next, combine the \( y \) terms: \[ \frac{1}{6}y + \frac{3}{6}y = \frac{4}{6}y \]
Now simplify \( \frac{4}{6} \): \[ \frac{4}{6} = \frac{2}{3} \] So, \( \frac{4}{6}y = \frac{2}{3}y \).
-
Now, put the simplified terms together: \[ \frac{3}{5}x + \frac{2}{3}y \]
Thus, the simplified expression is: \[ \frac{3}{5}x + \frac{2}{3}y \]